Area-level socioeconomic context, total mortality and cause-specific mortality in Spain: Heterogeneous findings depending on the level of geographic aggregation. (September 2015) - Regidor, Enrique; Vallejo, Fernando; Reques, Laura; Cea, Lucía; Miqueleiz, Estrella; Barrio, Gregorio
Abstract: The objective of this study was to estimate the association between area-level socioeconomic context and mortality in Spain, using two different geographic aggregations. Nation-wide prospective study covering all persons living in Spain in 2001. Mortality was analysed in Spanish citizens by province of residence and in citizens of Madrid by neighbourhood of residence. Provinces and neighbourhoods were grouped into quartiles according to two socioeconomic indicators: percentage of the population with university education and unemployment rate. The measure of association was the rate ratio for total mortality and cause-specific mortality, by each socioeconomic indicator in two age groups, 25–64 years (adult population) and 65 years and over (elderly population). After adjustment for all individual socioeconomic variables, the rate ratio for total mortality among residents in the provinces with the worst versus best socioeconomic context was 0.92 (95% CI 0.88–0.97) when the indicator was percentage of university population and 0.89 (0.85–0.93) when it was unemployment rate in the adult population, and 1.05 (1.00–1.11) and 1.08 (1.03–1.13), respectively, in the elderly population. No significant differences in mortality were observed between adults residing in neighbourhoods with the worst versus best socioeconomic context, but in the elderly population the mortality rate ratios for the two socioeconomic indicators were 1.04 (1.01–1.07) and 1.06 (1.03–1.09), respectively. Residents in provinces with the worst socioeconomic context had the lowest mortality from cancer and external causes and the highest mortality from cardiovascular diseases, while residents in neighbourhoods with the worst socioeconomic context had the highest mortality from respiratory and digestive diseases. Further research should find out the reasons for the lower total mortality in adult population residing in the Spanish provinces with the most adverse socioeconomic context and the reasons for excess mortality from digestive diseases and respiratory diseases among residents in neighbourhoods with the worst socioeconomic context. Highlights: Relation between socioeconomic context and mortality shows lack of consistency. Variation in the level of geographic aggregation used could be an explanation. Provinces with the worst socioeconomic context showed the lowest total mortality. Socioeconomic context of neighbourhood was not related with total mortality. Cause-specific mortality pattern varies depending of geographic aggregation used.